2023
DOI: 10.3390/membranes13050503
|View full text |Cite
|
Sign up to set email alerts
|

Electrokinetic and Electroconvective Effects in Ternary Electrolyte Near Ion-Selective Microsphere

Abstract: The paper presents theoretical and experimental investigations of the behavior of an electrolyte solution with three types of ions near an ion-selective microparticle with electrokinetically and pressure-driven flow. A special experimental cell has been developed for the investigations. An anion-selective spherical particle composed of ion-exchange resin is fixed in the center of the cell. An enriched region with a high salt concentration appears at the anode side of the particle when an electric field is turn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Georgy S. Ganchenko et al [ 1 ] presents theoretical and experimental investigations of the behavior of an electrolyte solution with three types of ions near an ion-selective microparticle with electrokinetically driven and pressure-driven flows. They found that an enriched region with a high salt concentration appears at the anode side of the ion exchange bead when an electric field is turned on.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Georgy S. Ganchenko et al [ 1 ] presents theoretical and experimental investigations of the behavior of an electrolyte solution with three types of ions near an ion-selective microparticle with electrokinetically driven and pressure-driven flows. They found that an enriched region with a high salt concentration appears at the anode side of the ion exchange bead when an electric field is turned on.…”
mentioning
confidence: 99%
“…The mathematical modeling of the relationships between the structure-transport properties of membranes and of the transfer and selectivity phenomena in an electric field or in its absence; • Commercial, experimental and modified ion exchange membranes (monopolar, bipolar, mosaic, composite, multilayer, organic, inorganic, homogeneous, heterogeneous, etc. ); Georgy S. Ganchenko et al [1] presents theoretical and experimental investigations of the behavior of an electrolyte solution with three types of ions near an ion-selective microparticle with electrokinetically driven and pressure-driven flows. They found that an enriched region with a high salt concentration appears at the anode side of the ion exchange bead when an electric field is turned on.…”
mentioning
confidence: 99%